DIODE LASER TREATMENT AS AN ALTERNATIVE TO ANTIBIOTIC PREMEDICATION - Licht, Frank (European Scientific Journal, ESJ, 2014)
Lasers used in the treatment of periodontal therapy are becoming more prevalent in dental offices. Patients with periodontal disease see extensive improvements in their periodontal status and overall health with laser therapy. Studies have shown a decreased prevalence in oral bacteria following these treatments (Moritz et al., 1998). Dental lasers in the treatment of periodontal disease can reduce significantly the bacterial population in the gingival tissue, theoretically reducing the need for antibiotic premedication (Kamma, Vasdekis, & Romanos, 2006). Future research in this area can provide the groundwork for the advancement of laser therapy in all aspects of medicine as well.